The Way We Organize Ourselves. - Grier, David Alan (Computer (00189162), 2013)
The value of programming as an educational discipline goes far beyond the desire not to live in ignorance. The Web extra at http://youtu.be/1AoX0HSIZv8 is a video segment in which author David Alan Grier expands on his Errant Hashtag column, in which he discusses the value of code and how it intersects with music and education through analysis, sequencing, and synthesis.